Abdulrahimova, Tarana - (:unkn) unknown (My University, 2026)
She graduated from the Azerbaijan University of Architecture and Construction in 1989. In 1983, she began her professional career as a technician at the Baku branch of the State Theatre Design Institute in Leningrad. From 1985 to 2003, she worked at the Azerbaijan Water Management Design Institute, where she held the positions of technician, senior technician, and First-Class Design Engineer in the Department of Architecture and Construction. In 2009, she joined the Department of Design at the Azerbaijan University of Architecture and Construction as a Senior Laboratory Assistant. In 2011, she was appointed Assistant Lecturer at the same department, and in 2016, she was promoted to the position of Senior Lecturer. In 2014, she successfully defended her doctoral dissertation and was awarded the degree of Doctor of Philosophy (PhD) in Architecture. Since 2022, she has been a faculty member of the Department of Environmental Design. To date, she has authored two methodological manuals, one teaching manual, and approximately 40 scientific publications. Her research has been published in national and international academic journals, including those published in Ankara, Moscow, Tbilisi, and Almaty.